2022
DOI: 10.32604/jrm.2021.016152
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antioxidant Packaging Film Based on Chinese Bayberry Tannin Extract and Polyvinyl Alcohol

Abstract: The current work explores the potential use of commercial Chinese bayberry tannin (BT) to develop antioxidant PVA-based films using solvent casting process for packaging applications. The effect of BT concentration on opacity, water resistance and antioxidant capacity of resulting films was investigated. Properties like tensile strength, thermal behavior, and morphological aspects were also characterized. The experimental results showed that PVA/BT films formed with uniformly brown color and generally good tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This can be attributed to an increase in void volume as a result of the destruction of the compact film network brought about by the aggregation of the constituents of the extract . This can consequently influence the channel of water vapor through the films . The WS of the films increased from 33.19 ± 1.48% for PP to 37.59 ± 1.88, 40.25 ± 1.33, and 46.49 ± 2.39% for PE1, PE5, and PE10, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to an increase in void volume as a result of the destruction of the compact film network brought about by the aggregation of the constituents of the extract . This can consequently influence the channel of water vapor through the films . The WS of the films increased from 33.19 ± 1.48% for PP to 37.59 ± 1.88, 40.25 ± 1.33, and 46.49 ± 2.39% for PE1, PE5, and PE10, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This may be caused by the formation of hydrogen and covalent bonds between PVA and the polyphenols present in the extract, resulting in a delay in the decomposition of main polymer chains. 36 3.3. Solubility and Water Vapor Permeability.…”
Section: Optical and Thermal Properties Of Filmsmentioning
confidence: 99%
“…The radical scavenging assay of DPPH was studied to estimate the antioxidant activity as previously reported in our previous works [ 36 , 37 ]. Initially, 0.1 g of the tested sample was immersed in 30 mL of distilled water while magnetic stirring was applied for 30 min.…”
Section: Characterizationmentioning
confidence: 99%
“…Our previous studies have shown that Chinese bayberry tannin (BT) presented a good antioxidant function of BT incorporated into PVA films [ 36 , 37 ]. However, the imperfect miscibility and weak covalent bonds of two components were generally found, even with the help of aldehydes, due to the large molecular weight of BT, which makes its incorporation into PVA more difficult compared with other polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…This posed a great motivation to replace phenolic compounds with tannins in a wide range of applications [1][2][3][4][5][6]. Recent studies have conducted successful preparations of tannin resin-based adhesives [7], foam materials [8], abrasion-resistive grinding wheel materials, film materials [9] and impregnated adhesives for papers and fibers [10,11].…”
Section: Introductionmentioning
confidence: 99%